CHALLENGES OF PRIVATIZATION IN THE POLISH HOSPITAL SECTOR - Rudawska, Iga (Journal of European Economy, 2018)
The structure of the Polish hospital sector calls for changes due to exploding health care costs, legal situation of the involved institutions, and demographic development. The paper explores the actual situation in the hospital sector in Poland and highlights the possible options of privatization. The author focuses on the would-to-be effects for each privatization alternative in terms of management, human resources and service quality. The paper also presents the debate over privatization of public hospitals, which seems to be among the most difficult political decisions.